MEASUREMENT OF PROMPT GAMMAS OF INELASTIC SCATTERING IN D2O SPHERE USING AMBE SOURCE. Issue 9 (22nd August 2022) - Czakoj, Tomáš; Košťál, Michal; Novák, Evžen; Losa, Evžen; Šimon, Jan; Schulc, Martin; Matěj, Zdeněk
Abstract: The inelastic neutron scattering is often followed by the emission of gamma photon. As the prompt gammas have a discrete level character they can be used for the identification of nuclides. Because of this fact, a good knowledge of photon production from inelastic scattering is important. Described research deals with the measurement of gamma originated from inelastic scattering of neutrons on 16 O. The 241 Am–Be was used as a neutron source because of its high average neutron energy. The oxygen in form of heavy water was used for maximization of neutron flux on oxygen and minimization of background gammas' production, namely 2223 keV gammas accompanying capture on hydrogen 1 H. The gamma spectrum was measured by HPGe and the stilbene detector. The HPGe measured quantities are comparted with calculation and discrepancies between measured and calculated gamma fluxes are reported. Stilbene measurement shows indistinguishability of gamma peaks above 6 MeV.